Can individual patients assess differences in quality of life between groups of patients?. (27th August 2013) - Cocks, K.; Velikova, G.; King, M.T.; Fayers, P.M.; Brown, J.M.
<x xml:space="preserve">Abstract</x> This qualitative study piloted a method for eliciting patient opinion on the size of group differences in quality of life (QOL) scores from the EORTC QLQ‐C30. Using scenarios from published studies, patients were asked the differences in QOL they would expect between two groups of patients or a group of patients over time. Interviews were transcribed verbatim and thematic analysis used. Eleven breast cancer patients were interviewed. The final thematic framework consisted of three major themes: (1) their ability to use published data to judge the size of differences in QOL scores, (2) their ability to gain familiarity and understanding of the QLQ‐C30 questionnaire in an interview situation and (3) their ability to understand and assess differences from a group of patients rather than on an individual basis. Patients felt able to understand the questionnaire and scoring. They provided an opinion on whether differences in QOL scores were trivial, small, medium or large. Patient perspectives were often based on their own experience of the disease and treatments and their opinions were varied. In order to estimate clinically meaningful differences from published literature, a larger number of patients with varied experiences would be required and a consensus process used to align opinions where possible.